Revitalisasi Nilai-Nilai Kewarganegaraan sebagai Fondasi Pembangunan Berkarakter di Kota Surakarta: (Sebuah Studi Pustaka) - Daffa Jihadan Al Haqqi; Nabila Dwi Agustina; Wirda Rohmah (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
Revitalizing civic values ​​is a strategic step in strengthening the nation's character, which is based on morals, integrity, and a strong personality, especially in Surakarta City. Amidst the rapid flow of globalization and technological development, noble values ​​such as mutual cooperation, tolerance, social responsibility, and love of the homeland have begun to experience a shift in meaning. This study aims to analyze efforts to strengthen civic values ​​as the basis for character development in Surakarta. Using a qualitative descriptive approach, this study explores the contributions of local governments, educational institutions, and the community in instilling Pancasila values ​​and civic ethics in social life. The results show that the application of civic values ​​through education, community activities, and public policies can shape citizens who are disciplined, caring, and respectful of diversity. Cooperation between the government, schools, and the community is a key factor in strengthening morality and national spirit. The revitalization of civic values ​​in Surakarta City has been proven to support the realization of a society with character, harmony, and a focus on sustainable development.